The Educational Turn in Contemporary Art : Historical Precedents and Defining Characteristics of Participatory Pedagogy-Based Art - 이은지(Eunji J. Lee) (Journal of Basic Design & Art, 2023)
The educational turn in contemporary art signifies a recent trend in contemporary artmaking and curatorial practices focused on generating knowledge structures through art. Artists who align with this movement often create their artworks by employing educational methods and formats such as lectures, workshops, and institutional platforms, in order to raise critical awareness of social issues and elicit change among audience members. These participatory pedagogy-based artworks have significant educational implications as they demonstrate various modes of learning through art and enhance the aesthetic experiences of participants. Hence, from an art educator’s perspective, this study aims to trace the historical roots of such pedagogy-based participatory artworks and highlight their key characteristics. The theoretical foundation of the study draws from writings of contemporary art critics Claire Bishop, Nicolas Bourriaud, Grant Kester, and Tom Finkelpearl, along with educational theories of John Dewey, a proponent of progressive education and social reconstructionism. Artist Joseph Beuys is explored as a pioneering figure in this genre, whose lecture-performances, socially engaged art, and environmental works have significantly influenced subsequent pedagogy-based art practices that have emerged since the mid-1990s. The study identifies five defining characteristics of such artworks through firsthand observations and literature reviews: 1) Time frame: durational and temporary, 2) Dialogue based on critical pedagogy, 3) Collaborative group work, 4) Lecture-performance, and 5) Alternative schools, illustrated with exemplary artworks. Overall, this study underscores the social and educational implications of contemporary art, with a particular focus on participatory pedagogy-based art practices as an intersection of the fields of contemporary art and education. KCI Citation Count: 0